GENETIC DIVERSITY, GROWTH AND CARRAGEENAN QUALITY OF KOTONI (RED SEAWEED) ACROSS THREE CULTIVATION SITES IN EASTERN INDONESIA - Fadilah, Siti; Pong-Masak, Petrus Rani; Farman, Aditia; Ratnawati, Pustika (Agency for Marine and Fisheries Extension and Human Resources, 2024)
Indonesia is a leading global producer of seaweed, with kotoni seaweed highly valued for its high-quality carrageenan, an essential ingredient in various industries. This study aimed to evaluate the growth, carrageenan quality, and genetic diversity of kotoni seaweed cultivated at three distinct sites in eastern Indonesia: Banggai, West Halmahera, and Biak. The research involved cultivating kotoni seaweed over a 45-day period using the long-line technique, with growth monitoring conducted every five days and water quality parameters measured concurrently. Additionally, ex situ analyses of nitrate, phosphate, and ammonia were performed every 15 days. Carrageenan quality was assessed by measuring carrageenan content, gel strength, and viscosity, in addition to proximate composition analysis. Genetic diversity was evaluated using the cytochrome oxidase subunit 1 (COI) gene, involving DNA extraction, PCR amplification, and sequencing to determine genetic similarity across the cultivation sites. Significant differences in growth rates and carrageenan quality were observed across the three sites. West Halmahera exhibited the highest growth rate, making it the most favorable site for large-scale seaweed cultivation. Although Biak had a lower growth rate, it produced carrageenan with superior gel strength and viscosity, indicating higher product quality. Genetic analysis confirmed 100% similarity among the samples across sites. These findings underscore the importance of site-specific cultivation practices to optimize both yield and carrageenan quality, supporting the sustainability and economic viability of kotoni seaweed cultivation in Indonesia.